2020
DOI: 10.1186/s12882-020-02010-5
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional nationwide survey of congenital and infantile nephrotic syndrome in Japan

Abstract: Background: Congenital nephrotic syndrome (CNS) and infantile nephrotic syndrome (INS) cause substantial morbidity and mortality. In Japan, there is a lack of knowledge regarding the characteristics of CNS and INS. This study aimed to clarify the characteristics of CNS and INS in Japan. Methods: This cross-sectional nationwide survey obtained data from 44 institutions in Japan managing 92 patients with CNS or INS, by means of two survey questionnaires sent by postal mail. Patients aged < 16 years by 1 April 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Up to 30.0% (9/30) of the patients did not receive appropriate treatment after genetic diagnosis because their parents declined treatment due to the high financial burden involved or concerns about poor prognosis. A cross-sectional nationwide survey of CNS and infantile NS in Japan reported that up to 78.8% (26/33) of patients underwent peritoneal dialysis and up to 51.5% (17/33) underwent subsequent renal transplantation ( 25 ). On the one hand, due to the very low frequency of renal disease resulting from NPHS1 variants, individuals and general clinicians are unfamiliar with the disorder as well as its prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to 30.0% (9/30) of the patients did not receive appropriate treatment after genetic diagnosis because their parents declined treatment due to the high financial burden involved or concerns about poor prognosis. A cross-sectional nationwide survey of CNS and infantile NS in Japan reported that up to 78.8% (26/33) of patients underwent peritoneal dialysis and up to 51.5% (17/33) underwent subsequent renal transplantation ( 25 ). On the one hand, due to the very low frequency of renal disease resulting from NPHS1 variants, individuals and general clinicians are unfamiliar with the disorder as well as its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the phenotype and genotype in CNS patients with NPHS1 variants in this study with the other four cohorts reported in the literature(23)(24)(25)(26) is shown in…”
mentioning
confidence: 83%
“…Nephrotic syndrome (NS) is the most common glomerular disease in children, characterized by massive proteinuria, serum hypoalbuminemia, and edema. Venous thromboembolism (VTE) and serious complications including cerebral venous sinus thrombosis and pulmonary thromboembolism have been reported in approximately 3% of pediatric NS [ 1 12 ]. The mechanism(s) that cause VTE in NS remains to be elucidated, however, and the establishment of prophylactic antithrombotic therapy could be highly beneficial.…”
Section: Introductionmentioning
confidence: 99%